The association between multimorbidity patterns and physical frailty among middle-aged and older community-dwelling adults: the mediating role of depressive symptoms - Geng, Yuhan; Zhou, Ming; Liu, Yangxiaoxue; Zhao, Tianshu; Zhang, Jiali; Xin, Min; Wang, Wenxin; Zhang, Gongzi; Huang, Liping (Frontiers in Public Health, 2025)
BackgroundThis study aimed to investigate the association between multimorbidity and frailty, and the potential mediating role of depressive symptoms in Chinese middle-aged and older community-dwelling adults.MethodsWe selected a total of 5,232 adults with two or more chronic diseases from the China Health and Retirement Longitudinal Study (CHARLS) database. Clusters of participants with similar multimorbidity patterns were identified through fuzzy c-means cluster analyses. The cross-sectional association between multimorbidity and frailty was measured through logistic regression analyses. Mediation analysis was applied to examine direct and indirect associations within the counterfactual framework.ResultsAt baseline, we identified five multimorbidity patterns. Two of these patterns significantly increased the risk of frailty compared to a non-specific pattern. Depression mediated 35.20% of the effect of multimorbidity on frailty (p = 0.042). Notably, in adults aged 60 years and older, this mediation accounted for 69.84% of the total effect, surpassing the direct impact of multimorbidity on frailty. Among individuals with economic support (0.020, 95% CI: 0.002–0.040), high school education (0.062, 95% CI: 0.007–0.120), and no alcohol consumption (0.024, 95% CI: 0.003–0.050), depression entirely mediated the impact of comorbidities.ConclusionThis study reveals strong links between specific multimorbidity patterns and physical frailty, with depression significantly mediating these effects, particularly in certain populations. Findings emphasize tailored mental health interventions’ necessity in specific groups.